Technological integration to reactivate paralyzed organizations - Romagnano, María Gema (2023)
The new way of sharing, communicating, storing, personal assisting, and even purchasing products or services, gender millions of data. In any application domain, this data will process and converted into information. The conversion implies the complementary relationship between several disciplines. A successful example occurs between the Internet of Things (IoT), Computational Intelligence (CI), Data Mining (DM), and Big Data (BD). Globally, various studies cases combined IoT, CI, DM, and BD. So, some sectors that provide services have a more advanced interaction, for example, the health with monitoring and detection, diagnostic and care technologies. In other service sectors, however, technological advances have not evolved at the same rate. A specific case in Argentina is long-distance land transport. This paper presents a plan and guide, combining different devices and technologies to reactivate this type of organization. We propose the integration of IoT, CI, Business Intelligence (BI), and Business Analytics (BA). Also, we experiment, in the transportation sector, with different algorithms and software to analyze images and data. Finally, we get conclusions about the proposed strategy.